2019
DOI: 10.1155/2019/4609702
|View full text |Cite
|
Sign up to set email alerts
|

Iron Redox Chemistry and Implications in the Parkinson’s Disease Brain

Abstract: The etiology of Parkinson's disease (PD) is linked with cellular inclusions in the substantia nigra pars compacta region of the brain that are enriched in the misfolded presynaptic protein α-synuclein (αS) and death of the dopaminergic neurons. Brain iron homeostasis governs both neurotransmission and neurodegeneration; hence, the role of iron in PD progression and neuronal health is apparent. Elevated iron deposits become prevalent in the cerebral region upon aging and even more so in the PD brain. Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 109 publications
(141 reference statements)
0
23
0
Order By: Relevance
“…Conversely, there are many indications that iron overload and presence of unbound iron in cellular structure have deleterious consequences on mental health. Indeed, excessive iron deposits become prevalent in the cerebral region upon ageing and even more so in the brains of subjects suffering from Parkinson disease [179] or Alzheimer disease [180] diseases, where they are associated with the neurodegeneration observed in these pathologies.…”
Section: Intake or Status In Vitamin C Iron Magnesium And Zinc And mentioning
confidence: 99%
“…Conversely, there are many indications that iron overload and presence of unbound iron in cellular structure have deleterious consequences on mental health. Indeed, excessive iron deposits become prevalent in the cerebral region upon ageing and even more so in the brains of subjects suffering from Parkinson disease [179] or Alzheimer disease [180] diseases, where they are associated with the neurodegeneration observed in these pathologies.…”
Section: Intake or Status In Vitamin C Iron Magnesium And Zinc And mentioning
confidence: 99%
“…Moreover, the reduction of the GSH levels and higher oxidative stress promote the aggregation of the α-synuclein protein [47]. According to some studies, that GSH supplementation led to the dissolution of the α-synuclein aggregates as well as to an increase in the GSH levels in the brains of rats with induced PD [48]. Clinical studies based on NMR proved the involvement of GSH in multiple sclerosis.…”
Section: Glutathionementioning
confidence: 99%
“…Fe II supplementation resulted in a moderate decrease in the overall fluorescence emission of dityrosine crosslinks within NAc WT, while Fe III supplementation enhanced overall dityrosine crosslinking in NAc WT. Iron is thought to bind within the C-terminal region of NAc αSyn [9,18,24], within close proximity to the three C-terminal tyrosine residues. Previously, we reported that Fe blocks Cu-induced photoinitiated dityrosine crosslinking in NAc αSyn [23], and our current results further suggest that Fe II also results in a relative decrease in dityrosine crosslinking compared to the unmetalated native protein.…”
Section: Photoinduced Dityrosine Formation Of Fe-bound Nac αSyn Variantsmentioning
confidence: 99%
“…In contrast, Fe III coordination to NAc WT promotes a conformation of NAc αSyn that facilitates photoinitiated dityrosine crosslinking. Pathological concentrations of iron accumulate within the substantia nigra of PD afflicted patients [18]. To map the structural impact of iron coordination to NAc αSyn, NAc WT and each of the NAc αSyn tyrosine mutants were subjected to stoichiometric ratios of iron in both the Fe II and Fe III redox states (Figure 3).…”
Section: Photoinduced Dityrosine Formation Of Fe-bound Nac αSyn Variantsmentioning
confidence: 99%
See 1 more Smart Citation